Letter: oesophageal histological abnormalities and GERD ‐ an underestimated relationship requiring more attention. Issue 1 (11th December 2017) - Savarino, E.; Lorenzon, G.; Facchin, S.; Savarino, V.
Abstract : Linked Content This article is linked to Vakil et al paper. To view this article visit https://doi.org/10.1111/apt.14028 .